698 ENDOLUMINAL VACUUM THERAPY (EVT) AS A TREATMENT FOR ESOPHAGEAL LEAKS; 10-YEARS' EXPERIENCE FROM A TERTIARY UK ESPHAGOGASTRIC CENTRE. (17th September 2021) - Afzal, Zeeshan; Gourgiotis, Stavros; Hardwick, Richard; Safranek, Peter; Sujendran, Vijay; Bennett, John; O'Neill, Robert; Noorani, Ayesha; Hindmarsh, Andrew
Abstract:  : Esophageal leaks present a significant management challenge, especially in patients with delayed presentation and established sepsis. Endoluminal vacuum therapy (EVT) is an emerging treatment strategy which may reduce morbidity and mortality compared to traditional treatments in this patient group. We report the outcomes for patients with esophageal leaks from a range of different causes that were treated with EVT in a tertiary UK hospital over a 10-year period. Methods: Between April 2011 and March 2021, 45 patients with a median age of 67 years (31–92) who had an esophageal leak were treated with EVT. All patients were treated with an ad-hoc endoluminal vacuum device (EVD) constructed using V.A.C GRANUFOAMTM (KCI) and a standard nasogastric (Ryles) tube. The median Apache II score for patients at the time of leak diagnosis was 20 (6–36). The cause of the leak was anastomotic in 16 patients (36%), iatrogenic in 14 patients (31%), spontaneous in 14 patients (31%), and traumatic in 1 patient (2%). Information related to treatment and outcome was recorded prospectively. Results: Successful resolution of the leak was achieved in 39 (87%) patients. The median number of EVD changes required to heal the leak was 6 (1–17). There were no complications related to insertion of the EVD. The median length of hospital stay was 49 days (1–108). Six (13%) patients died during treatment. Six (13%) patients had complications during treatment requiring further intervention; 2 (4%) had a significant bleed requiring angiography and aortic stent placement, 1 (2%) had a stroke, 1 (2%) had a pulmonary embolism, 1 (2%) had a myocardial infarction, and 1 (2%) contracted COVID-19. Conclusion: EVT is a safe and effective treatment that can be used successfully to treat esophageal leaks from a disparate range of leak causes in selected critically unwell patients. Further studies are required to develop a standardized procedure and management pathway which will enable broader adoption of EVT in this group of patients.